The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3934/dcdsb.2018331
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic one layer shallow water equations with Lévy noise

Abstract: Dedicated to Peter Eris Kloeden on the occasion of his 70 th birthday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…In the case one of section 4, we have shown that the jump noises with large positive coefficients can force the population for equation (1) to be extinct with probability one. Interestingly, we have found in the case two of section 4 that the jump noises with positive coefficients facilitate the permanence of the specie for equation (6).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the case one of section 4, we have shown that the jump noises with large positive coefficients can force the population for equation (1) to be extinct with probability one. Interestingly, we have found in the case two of section 4 that the jump noises with positive coefficients facilitate the permanence of the specie for equation (6).…”
Section: Discussionmentioning
confidence: 83%
“…From Theorem 2.7, we can obtain the following conclusions: (a) If h(t, z) > 0 for t ≥ 0 and z ∈ Z, the jump noises are favorable for the permanence of equation 6; (b) If −1 < h(t, z) < 0 for t ≥ 0 and z ∈ Z, the jump noises are unfavorable for the permanence of equation (6).…”
Section: Remarkmentioning
confidence: 94%
See 1 more Smart Citation
“…Note that in Lemma 4.14 and in Lemma 4.15 we do not obtain convergence of the mentioned processes in L 2 ( Ω; L 2 ([0, T ]; H)) as in e.g. [15] or [19]. The lack of such a result could pose a problem while passing to the limit n → ∞ in Step 2.…”
Section: Estimates In Fractional Sobolev Spacesmentioning
confidence: 89%
“…Interest in SPDEs with Lévy noise has been growing in the recent years, see e.g., [12], [17], [15], [42], [43]. In [13] and [52] the authors use processes with jumps to model phase transitions in bursts of wind that contribute to the dynamics of El Niño.…”
Section: Introductionmentioning
confidence: 99%